Exposure to prescription opioid analgesics in utero and risk of neonatal abstinence syndrome: population based cohort study. (14th May 2015) - Desai, Rishi J; Huybrechts, Krista F; Hernandez-Diaz, Sonia; Mogun, Helen; Patorno, Elisabetta; Kaltenbach, Karol; Kerzner, Leslie S; Bateman, Brian T
Abstract : Objective To provide absolute and relative risk estimates of neonatal abstinence syndrome (NAS) based on duration and timing of prescription opioid use during pregnancy in the presence or absence of additional NAS risk factors of history of opioid misuse or dependence, misuse of other substances, non-opioid psychotropic drug use, and smoking. Design Observational cohort study. Setting Medicaid data from 46 US states. Participants Pregnant women filling at least one prescription for an opioid analgesic at any time during pregnancy for whom opioid exposure characteristics including duration of therapy: short term (<30 days) or long term (≥30 days); timing of use: early use (only in the first two trimesters) or late use (extending into the third trimester); and cumulative dose (in morphine equivalent milligrams) were assessed. Main outcome measure Diagnosis of NAS in liveborn infants. Results 1705 cases of NAS were identified among 290 605 pregnant women filling opioid prescriptions, corresponding to an absolute risk of 5.9 per 1000 deliveries (95% confidence interval 5.6 to 6.2). Long term opioid use during pregnancy resulted in higher absolute risk of NAS per 1000 deliveries in the presence of additional risk factors of known opioid misuse (220.2 (200.8 to 241.0)), alcohol or other drug misuse (30.8 (26.1 to 36.0)), exposure to other psychotropic medications (13.1 (10.6 to 16.1)), and smoking (6.6 (4.3 to 9.6)) than in the absence of any of these risk factors (4.2 (3.3 to 5.4)). The corresponding risk estimates for short term use were 192.0 (175.8 to 209.3), 7.0 (6.0 to 8.2), 2.0 (1.5 to 2.6), 1.5 (1.0 to 2.0), and 0.7 (0.6 to 0.8) per 1000 deliveries, respectively. In propensity score matched analyses, long term prescription opioid use compared with short term use and late use compared with early use in pregnancy demonstrated greater risk of NAS (risk ratios 2.05 (95% confidence interval 1.81 to 2.33) and 1.24 (1.12 to 1.38), respectively). Conclusions Use of prescription opioids during pregnancy is associated with a low absolute risk of NAS in the absence of additional risk factors. Long term use compared with short term use and late use compared with early use of prescription opioids are associated with increased NAS risk independent of additional risk factors.